Marketing in tourism, hospitality, events and food a critical approach - Hirst, Craig; Tresidder, Richard (Goodfellow Publishers, 2016)
"Targeted at second year undergraduate students through to master's level post-graduate, Marketing in Tourism, Events and Food 2nd edition takes the reader through a logical examination of key marketing debates, theories and approaches and encourages them to explore their own thoughts, ideas and opinions. It analyses areas such as marketplace value and value creation, consumers and consumption, taste and identity, sustainability and power, as well as semiotics and commercial myth making, and offers a contemporary examination of these industry sectors with experiential aspects of marketing and productive consumption playing an important role throughout"--Provided by publisher.